Resposta:
[tex] {2}^{ - 1} + 6 \times ( \frac{2}{3})^{ - 2} - (( - \frac{1}{3} )^{ - 1} )^{ - 3} [/tex]
vc tem
- potências
- multiplicações
- soma
- subtração
- parênteses
vamos fazer por partes então
resolve primeiro as potencias
[tex] {2}^{ - 1} = \frac{1}{2} [/tex]
[tex]( \frac{2}{3})^{ - 2} =( \frac{ {2}^{2} }{ {3}^{2} }) ^{ - 1} = ( \frac{ 4 } { 9}) ^{ - 1} = \frac{9}{4} [/tex]
[tex] (( - \frac{1}{3} )^{ - 1} )^{ - 3} \\ = ( - \frac{1}{3} ) ^{( - 1) \times ( - 3)} \\ = ( - \frac{1}{3}) ^{ + 3} \\ = ( - \frac{1}{27} )[/tex]
agora vc tem...
[tex] { \frac{1}{2} } + 6 \times ( \frac{9}{4}) - ( - \frac{1}{27} ) \\ = \frac{1}{2} + \frac{27}{2} + \frac{1}{27} \\ = 14 + \frac{1}{27} = \frac{14 \times 27 + 1}{27} = \frac{379}{27} [/tex]